PSIKOLOGI KOMUNIKASI DAN KEKERASAN SEKSUAL PADA ANAK USIA DINI - Ekaningtyas, Ni Luh Drajati (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2020)
Data from the Online Information System for The Protection of Women and Children (SIMFONI-PPA) shows that the level of sexual assault in early childhood in Indonesia is very high and alarming. Although the government has promoted various programs to reduce the rate of sexual assault in early childhood, the facts show that the number of reported cases has increased every year, including during the COVID-19 pandemic. One of the key solutions to this problem is to establish effective communication with early childhood by applying a psychological approach. The application of psychology in communication will facilitate the efforts of parents in taking precautions through sex education, as well as in taking control or countermeasures through warm and open communication. The application of communication psychology for early childhood victims of sexual assault can be done by: (1) Maintain a tone of speech, (2) Speak directly, (3) Listen and follow up in children’s stories, (4) Do not blame and judge children, (5) Reassure children that they are innocent, (6) Patience, (7) Maintain self-calm, (8) Believe in children’s stories, (9) Restore children’s feeling of security, (10) Don’t let children blame themselves, (11) Be careful in expressing anger, (12) Seek expert help.